Geometagenomics illuminates the impact of agriculture on the distribution and prevalence of plant viruses at the ecosystem scale - Bernardo, Pauline; Charles-Dominique, Tristan; Barakat, Mohamed; Ortet, Philippe; Fernandez, Emmanuel; Filloux, Denis; Hartnady, Penelope; Rebelo, Tony A; Cousins, Stephen R; Mesleard, François; Cohez, Damien; Yavercovski, Nicole; et al. (The ISME Journal, 2018)
Disease emergence events regularly result from human activities such as agriculture, which frequently brings large populations of genetically uniform hosts into contact with potential pathogens. Although viruses cause nearly 50% of emerging plant diseases, there is little systematic information about virus distribution across agro-ecological interfaces and large gaps in understanding of virus diversity in nature. Here we applied a novel landscape-scale geometagenomics approach to examine relationships between agricultural land use and distributions of plant-associated viruses in two Mediterranean-climate biodiversity hotspots (Western Cape region of South Africa and Rhône river delta region of France). In total, we analysed 1725 geo-referenced plant samples collected over two years from 4.5 × 4.5 km 2 grids spanning farmlands and adjacent uncultivated vegetation. We found substantial virus prevalence (25.8–35.7%) in all ecosystems, but prevalence and identified family-level virus diversity were greatest in cultivated areas, with some virus families displaying strong agricultural associations. Our survey revealed 94 previously unknown virus species, primarily from uncultivated plants. This is the first effort to systematically evaluate plant-associated viromes across broad agro-ecological interfaces. Our findings indicate that agriculture substantially influences plant virus distributions and highlight the extent of current ignorance about the diversity and roles of viruses in nature.